NORMAL COORDINATE ANALYSIS OF THE ZERO-WAVE VECTOR VIBRATIONS OF Er Ba2 CU307 (Biological Sciences - PJSIR, 2022)
Using Wilson's FG matrix method, a normal coordinate analysis of the spectral frequencies and form of the zerowavevector vibrations of the high temperature superconductor Er Ba2Cu)07 have been performed, The vibrational frequenciesand potential energy distribution of 21 infrared active and IS Raman active modes are presented. The potentialconstants employed here are given and the evaluated vibrational frequencies are compared with the availableexperimental values.